Tricks of fortune - Chern, Lina (Chern, Lina. Play the fool mystery, 2025)
"Katie True has gotten her crap together . . . sort of. Now that the sinister events of the past year have wound down, Katie has finally made her dream come true and opened her own tarot reading room--even if it's in her sister's old real estate office in an outdoor strip mall. It's a good start, but her momentum grinds to a halt when the murder of beloved veteran police officer, Matthew Peterson, shakes her and her small community to the core. Katie is torn. Lieutenant Peterson had saved her life as a child and holds a special place in her past. Even worse, her closest friend Gina--who knows Katie better than she knows herself--is the primary suspect. As the investigation unfolds, the details surrounding Peterson's death become increasingly murky, as does Gina's innocence. All Katie knows is that following her intuition has gotten her this far. But will her trusty tarot deck help her when the truth about the people she loves is too terrible to face?"--